Segmented filamentous bacteria-based treatment to elicit protection against Enterobacteriaceae in Layer chickens - Meinen-Jochum, Jared; Ott, Logan C.; Mellata, Melha (Frontiers in Microbiology, 2023)
Gut microbes like segmented filamentous bacteria (SFB) play a key role in gut maturation during early life, as demonstrated in humans and mice. Our previous study demonstrated oral inoculation of ileumspores containing SFB to chickens after hatch increases early SFB gut colonization, which increases immune maturation and resistance to bacteria, like Salmonella, as tested in vitro; however, more studies are needed for treatment optimization and in vivo testing. The objectives of this study were to 1) test a treatment that includes both spores and filamentous SFB, 2) validate antimicrobial ability of the treatment in layer hens in vivo, and 3) elucidate its molecular mechanism. One-day-old specific pathogen-free layers (n = 12 per group) were orally treated with either PBS (CON) or SFB-based treatment (SFB). At 4 days post-inoculation (DPI), both CON and SFB groups were orally challenged with Salmonella Typhimurium. Total Enterobacteriaceae and Salmonella were examined by plating and enumeration in feces at 7,10 and 14 dpi; and in the ileum, cecum, and spleen at 16 dpi in euthanized birds. The presence and levels of SFB were determined from ilea scrapings via microscopy and qPCR, respectively. Relative gene expression of host-derived antimicrobial peptides and cytokines in the distal ileum was determined by RT-qPCR. At 10 and 14 dpi, a significant decrease in total Enterobacteriaceae was observed in the feces of the SFB group. At necropsy, the level of SFB was significantly higher in the SFB group than in the CON group, while a significant decrease in total Enterobacteriaceae and Salmonella was observed in the ceca of the SFB group. RT-qPCR revealed increased expression of 𝛽-defensin 14, and cytokines IL-10 and IFNg. The introduction of SFB at hatch as a prophylactic treatment may benefit commercial partners as well as consumers by reducing the incidence of Enterobacteriaceae in food animals. Reduction of these bacteria in animals would, in turn, increase animal health, productivity, and safety for consumers. Studies to optimize the treatment for poultry industry applications are ongoing in our lab.